New orchid species of Stigmatodactylus (Orchidoideae; Diurideae) and a new record of Cryptostylis carinata from central Palawan, Philippines - Robinson, Alastair S.; Gironella, Elizabeth P.; Cervancia, Jehson M. (Phytotaxa, 2016)
Two new species of Stigmatodactylus from Palawan Island in the Philippines are described and illustrated. The taxa, which represent the first records for the genus Stigmatodactylus in the Philippines, are restricted to the ultramafic peaks of central Palawan. Cryptostylis carinata, originally described from New Guinea, is also documented, representing a first record for this species in Palawan.